PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PADA CV PELANGI REX’S BAKERY - Putu Ardelia Febriana; Ni Putu Cempaka Dharmadewi Atmaja (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2024)
The increasingly high development of business growth in the business world makes competition between business actors increasingly tight and unavoidable. This makes producers think more critically, creatively and innovatively about the changes that occur. The aim of this research is to examine the influence of product quality, service quality and personal sales on purchasing decisions at CV Pelangi Rex's Bakery. This research uses multiple linear analysis methods using SPSS 26. The sampling method used is the probability sampling method with a simple random sampling approach. The population in this research was 100 respondents who were consumers of CV Pelangi Rex's Bakery. The results of the analysis show that product quality and personal selling variables have a positive and significant effect on purchasing decisions. This means that the better the product quality and personal selling provided, the greater the consumer's desire to make a purchase. Meanwhile, the service quality variable has no effect on purchasing decisions. This means that the quality of service provided has not been able to meet or even exceed consumer expectations when making purchasing decisions.